Preliminary evaluation of a novel serotype O foot-and-mouth disease mRNA vaccine - Zhao, Jingang; Xiao, Peng; Xin, Aiguo; Zhu, Heran; Wang, Hao; Xiao, Jinlong; Gao, Hong (Frontiers in Microbiology, 2025)
Foot-and-mouth disease virus (FMDV) is one of the most significant animal pathogens worldwide, severely impacting the health and productivity of pigs, cattle, sheep, and other ungulates. Although the traditional vaccines have played a crucial role in epidemic control, inactivated vaccines face persistent challenges concerning the potential for virus dissemination and pressures from serotype and subtype matching. However, the manufacture of attenuated vaccines is forbidden, and the efficiency of alternative vaccines for immune protection is still inadequate. Consequently, there exists an urgent need for safer and more effective innovative vaccines in animal husbandry. In this study, we aimed to develop a lipid nanoparticle mRNA vaccine based on VP1-3A-3D epitopes from serotype O FMD and to verify its specific expression within cytoplasmic and injection sites. Our findings demonstrated that mRNA transfected into primary spleen cells derived from guinea pigs induced cytokine release, promoted differentiation of both CD4+ T and CD8+ T lymphocytes, and enhanced lymphocyte proliferation rates. Following immunization of mRNA vaccine in guinea pigs, we observed increased differentiation of both CD4+ T and CD8+ T cells, alongside elevated levels of cytokine secretion. Additionally, this vaccination induced the production of specific IgG antibodies as well as neutralizing antibodies. Importantly, our vaccine provided complete protection for all six guinea pigs against a lethal challenge of 100 GPID50, with histopathological scores indicating protection equivalent to that conferred by the inactivated vaccine. The viral load results demonstrated that the vaccine group significantly reduced viral copy numbers in serum and effectively decreased the concentration of the inflammatory cytokine IL-1β. Furthermore, during the pre-immune phase following vaccination with the mRNA vaccine in pigs, heightened cytokine secretion was observed, along with the inhibition of viral replication. Simultaneously, the neutralizing antibody titer in the serum remained stable over 4 months. Immunofluorescence analysis of spleen tissues from both guinea pigs and pigs demonstrated marked activation and increased expression of CD4+ and CD8+ T lymphocytes, as well as macrophages, in the mRNA vaccine group. In summary, this study suggests that the serotype O FMD mRNA vaccine is a promising candidate for further development in the fight against FMDV.